Determination of Lipid Peroxidation and Fatty Acid Compositions in the Caviars of Rainbow Trout and Carp - Inanli, Ayse Gurel; Coban, Ozlem Emir; Yilmaz, Okkes; Ozpolat, Emine; Kuzgun, Nermin Karaton (Taylor & Francis Inc, 2018)
In this study, roes obtained from carp (Cyprinus carpio carpio) that were caught in Keban Dam Lake (Turkey) and cultured rainbow trout (Oncorhynchus mykiss) were processed as caviar, and the products were stored at + 4C degrees. Lipid peroxidation and the compositions of fatty acids of these products were assessed during production and storage period. The result of fatty analyses showed that palmitic acid (16:0), stearic acid (18:0), palmitoleic acid (16:1), oleic acid (18:1), eicosapentaenoic acid (EPA), and docosahexaenoic acid (DHA), which are all essential fatty acids, were determined in the caviars of the roes obtained from rainbow trout and carp. According to results of chemical analyses, there were no significant differences in thiobarbituric acid reactive substances (TBARs) between rainbow trout and carp caviars (p>0.05), but malondialdehyde (MDA) levels were found to be statistically significant (p<0.01). It can be concluded that caviars obtained from both rainbow trout and carp roes are rich in fatty acids and take a part in a balanced and healthy diet.
Keywords: Caviar; carp; trout; fatty acid; MDA; TBARs